Tourism SME sustainability social and economic challenges during pandemic: cases of Russian Federation, Georgia and Latvia - Bērziņa, Kristīne; Tsoy, Marina (E3S Web of Conferences, 2021)
. Until 2020, the tourism industry was characterized by a growth rate, the statistics highlight that globally 2019 was the tenth year with a consecutive annual growth. However, the Covid-19 pandemic marked a major turning point in the development of tourism, instead of tourism overdevelopment, the underdevelopment issues appeared in front pages of the industry news. The effects of the pandemic are intensified by the fact that tourism is a labour-intensive industry and that most companies in the sector are SMEs (small and medium sized enterprises). At this time, it is crucially important to look at sustainability issues, therefore the aim of this study is to analyse the social and economic dimensions of sustainability for tourism SMEs. Descriptive statistics as well as qualitative research methods were used to study the challenges posed by the pandemic, indepth interviews were conducted with tourism SMEs from three different countries. The conclusions show the situation from an enterprise perspective in Russian Federation, Georgia and Latvia
Keywords: Research Subject Categories::SOCIAL SCIENCES::Business and economics; development of tourism; Covid-19 pandemic